High performance thin layer chromatography fingerprint profile of ingredients and formulations of Shatavaryadi churna: an ayurvedic formulation - Puspendra Kumar; Shivesh Jha; Tanveer Naved (International Journal of Phytomedicine, 2013)
Objective: To develop the finger print of medicinally important ayurvedic formulation Shatavaryadi churna and its ingredients for presence of phytoconstituents in different extracts. Methods: Petroleum ether, chloroform, ethyl acetate and methanolic extract of all the ingredients and formulations were developed in the mobile phase n-hexane: diethyl ether (3:1), n-hexane: ethyl acetate: formic acid (6:4:0.2) n-hexane: ethyl acetate: formic acid (6:4:0.2) and toluene: ethyl acetate: formic acid (5:4:0.2) respectively using standard procedures and scanned under UV at suitable wavelength. Results: The HPTLC fingerprinting of all the extracts has shown several peaks with different Rf values. Conclusion: This fingerprint profile would be helpful in the identification and authentication of the selected ingredients and the formulations.